ANALISIS PENGARUH VARIASI TEGANGAN PADA METODE ANODIZING TERHADAP KETAHANAN KOROSI DAN KEKERASAN PERMUKAAN ALUMUNIUM TIPE SERI 6061: ANALYSIS OF THE EFFECT OF VOLTAGE VARIATIONS IN THE ANODIZING PROCESS ON THE CORROSION RESISTANCE AND SURFACE HARDNESS OF 6061 SERIES ALUMINUM - aziz huda; ZULFA KHALIDA; Devina Rosa (Mechanical Engineering Department Polinema Kediri, 2025)
Aluminum 6061 is susceptible to corrosion in aggressive environments despite its natural corrosion resistance. Anodizing effectively improves corrosion resistance and hardness; however, the effect of voltage variation requires further analysis. Research using voltages of 9V, 10V, 11V, and 12V showed that 10V resulted in the lowest corrosion current (1.456 × 10⁻⁸ A) and the highest polarization resistance 7,1474 × 10⁶, indicating optimal corrosion resistance. Hardness increased with voltage, reaching 49 HB at 12V. Voltage variation had a significant effect, with 10V being optimal for corrosion resistance and 12V for maximum hardness. This research are relevant for industries requiring a combination of high corrosion resistance and mechanical strength.